2018
DOI: 10.3390/catal8090347
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Aerogel-Supported Nickel and Iron for Gasification Gas Cleaning. Part I: Ammonia Adsorption

Abstract: Biomass gasification is a promising way to obtain “green energy”, but the gas composition makes it unsuitable for use in traditional technologies (i.e., IC engine). Gas purification over nickel and/or iron catalysts is an attractive alternative. Cellulose-based carbon aerogels (CAGs) have shown suitable physical chemical properties for use as catalyst supports. In this work, nickel and iron catalysts are supported on CAG made from cellulose microfibers. Microfibers were impregnated with (NH4)2SO4 to increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 85 publications
(114 reference statements)
1
9
0
Order By: Relevance
“…A third broad reflection can be observed around 15° which has already been identified in carbon aerogels from cellulose and it is related to the precursor. [ 6 ] This band has also been attributed to aliphatic chains bound to the edges of basal planes of the crystal structure. [ 45–47 ] A decrease in the intensity of this band is observed when the Pd content increases, suggesting the influence of the metal on the decomposition of the aliphatic chains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A third broad reflection can be observed around 15° which has already been identified in carbon aerogels from cellulose and it is related to the precursor. [ 6 ] This band has also been attributed to aliphatic chains bound to the edges of basal planes of the crystal structure. [ 45–47 ] A decrease in the intensity of this band is observed when the Pd content increases, suggesting the influence of the metal on the decomposition of the aliphatic chains.…”
Section: Resultsmentioning
confidence: 99%
“…These features make them promising materials in emergent fields of applications, such as energy storage, [ 1,2 ] electrocatalysis, [ 3 ] desalination, [ 4 ] bio‐sensing, [ 5 ] and gasification gas cleaning. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…18 This is the discovery of a special structure constructed from a network of nanosized particles that are interconnected and provide distinct gains for the fabrication of porous materials. 19,20 Interestingly, almost all of the outcomes of research revealed that organic aerogels used as catalyst supports in low-temperature fuel cell applications stabilize nanosized metal particles, resulting in a strong catalytic action. 21 The texture and pore size resulting in the synthesis method plays a significant role in providing robust catalytic support for fuel cell applications.…”
Section: F I G U R E 1 History Of Fuel Cell Technologymentioning
confidence: 99%
“…Different forms of aerogel structures, such as micropores, mesopores, and macropores, can be produced 18 . This is the discovery of a special structure constructed from a network of nanosized particles that are interconnected and provide distinct gains for the fabrication of porous materials 19,20 …”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 /CA was investigated as a photoelectrocatalyst for wastewater treatment (Jin et al, 2011). Ni/CA and Fe/CA were used as ammonia adsorption catalysts for gas purification (Gómez-Cápiro et al, 2018). SnO 2 /GA was used as a NO 2 gas sensor (Liu et al, 2014;Li et al, 2015).…”
Section: Introduction Aerogelsmentioning
confidence: 99%